Consanguinity and neonatal death: a nested case-control study. - Reza Chaman; Mahshid Gholami Taramsari; Ahmad Khosravi; Mohammad Amiri; Kourosh Holakouie Naieni; Masoud Yunesian (Tehran University of Medical Sciences, 2014)
Objective: Although numerous studies have found higher rates of abortion and still births following consanguinity (familial marriages), the question of whether consanguinity significantly increases the risk of neonatal death has inadequately been addressed.This study aims to evaluate familial marriage effects on neonatal death in rural areas in Iran. Materials and methods:I n this nested case-control study, 6900 newbornswho were born in rural areas of Kohgiluyeh and Boyerahmad Province (South-West of Iran)were followed till the end of neonatal period, and neonatal death was the outcome of interest. Subsequently 97 cases and 97 controls were selected in study cohort by using risk set sampling model. Crude and adjusted odds ratios (OR) were estimated by usinga conditional logistic regression model. Results:In the final model, prematurity (OR = 5.57), low birthweight (LBW) (OR = 7.68), consanguinity (first cousins) (OR = 5.23), C-section (OR = 7.27), birth rank more than 3 (OR = 6.95) and birthsinterval less than 24 months (OR = 4.65) showed significant statistical association with neonatal mortality (p < 0.05). Conclusion:According to our findings, after adjusting the effects of other significant risk factors, familial marriageto first cousins is considered asan important risk factor for neonatal death.